A new approach to textual criticism : an introduction to the coherence-based genealogical method - Wasserman, Tommy; Gurry, Peter J. (Resources for biblical study, 2017)
With the publication of the widely used twenty-eighth edition of Nestle-Aland's Novum Testamentum Graece and the fifth edition of the United Bible Society Greek New Testament, a computer-assisted method known as the Coherence-Based Genealogical Method (CBGM) was used for the first time to determine the most valuable witnesses and establish the initial text. This book offers the first full-length, student-friendly introduction to this important new method. After setting out the method's history, separate chapters clarify its key concepts such as genealogical coherence, textual flow diagrams, and the global stemma. Examples from across the New Testament are used to show how the method works in practice. The result is an essential introduction that will be of interest to students, translators, commentators, and anyone else who studies the Greek New Testament. --